The 2020 Royal Australian and New Zealand College of Psychiatrists clinical practice guidelines for mood disorders: Major depression summary. (27th December 2020) - Malhi, Gin S.; Bell, Erica; Singh, Ajeet B.; Bassett, Darryl; Berk, Michael; Boyce, Philip; Bryant, Richard; Gitlin, Michael; Hamilton, Amber; Hazell, Philip; Hopwood, Malcolm; Lyndon, Bill; et al.
Abstract: Objectives: To provide a succinct, clinically useful summary of the management of major depression, based on the 2020 Royal Australian and New Zealand College of Psychiatrists clinical practice guidelines for mood disorders (MDcpg 2020 ). Methods: To develop the MDcpg 2020, the mood disorders committee conducted an extensive review of the available literature to develop evidence‐based recommendations (EBR) based on National Health and Medical Research Council (NHMRC) guidelines. In the MDcpg 2020, these recommendations sit alongside consensus‐based recommendations (CBR) that were derived from extensive deliberations of the mood disorders committee, drawing on their expertise and clinical experience. This guideline summary is an abridged version that focuses on major depression. In collaboration with international experts in the field, it synthesises the key recommendations made in relation to the diagnosis and management of major depression. Results: The depression summary provides a systematic approach to diagnosis, and a logical clinical framework for management. The latter begins with Actions, which include important strategies that should be implemented from the outset. These include lifestyle changes, psychoeducation and psychological interventions. The summary advocates the use of antidepressants in the management of depression as Choices and nominates seven medications that can be trialled as clinically indicated before moving to Alternatives for managing depression. Subsequent strategies regarding Medication include Increasing Dose, Augmenting and Switching (MIDAS). The summary also recommends the use of electroconvulsive therapy (ECT), and discusses how to approach non‐response. Conclusions: The major depression summary provides up to date guidance regarding the management of major depressive disorder, as set out in the MDcpg 2020 . The recommendations are informed by research evidence in conjunction with clinical expertise and experience. The summary is intended for use by psychiatrists, psychologists and primary care physicians, but will be of interest to all clinicians and carers involved in the management of patients with depressive disorders.